Unveiling the genesis of the high catalytic activity in nickel phthalocyanine for electrochemical ammonia synthesis. Issue 25 (16th June 2021) - Murmu, Shyamal; Paul, Sourav; Kapse, Samadhan; Thapa, Ranjit; Chattopadhyay, Santanu; N., Abharana; Jha, Shambhu N.; Bhattacharyya, Dibyendu; Ghorai, Uttam Kumar
Abstract : DFT is applied to identify the active sites of NiPc for NRR and its catalytic origination. Accordingly, NiPc nanorods, synthesized by solvothermal method, exhibit NH3 yield rate of 85 μg h −1 mgcat −1 and FE of 25% at −0.3 V vs. RHE. Abstract : Electrochemical ammonia synthesis by the nitrogen reduction reaction (NRR) using an economically efficient electrocatalyst can provide a substitute for the Haber–Bosch process. However, identification of active sites responsible for the origin of catalytic activity in transition metal phthalocyanine is a difficult task due to its complex structure. Herein, density functional theory (DFT) is applied to identify the probable active sites of nickel phthalocyanine (NiPc) for the NRR as well as the origin of catalytic activity which is associated with the d band center and density of states (DOS) of Ni in NiPc. Accordingly, NiPc nanorods (NRs), synthesized by a solvothermal method in large scale, exhibit an NH3 yield rate about 85 μg h −1 mgcat −1 and a faradaic efficiency (FE) of 25% at −0.3 V vs. RHE. Moreover, the catalyst shows long term stability up to 30 hours while maintaining the NH3 yield and FE. The isotopic labelling experiment and other control investigation led to validation of the nitrogen source in NH3 formation. This study provides brand new insightful understanding of the active sites and the origin of the catalytic activity of NiPc for their NRR applications.